2004
DOI: 10.1111/j.1469-7610.2004.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention and memory biases in the offspring of parents with bipolar disorder: indications from a pilot study

Abstract: Thus, children without a mood disorder who are at high risk for developing a mood disorder were found to exhibit biases in attention and memory that are similar to those found for bipolar and unipolar depressed adults, suggesting that children at increased risk for affective disorder are characterized by potentially pathogenic cognitive structures that can be activated by sad mood. These findings offer insights into mechanisms of cognitive vulnerability for bipolar disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 63 publications
6
42
0
2
Order By: Relevance
“…In these circumstances, the attentional preference toward threatening stimuli would increase the BD patients 0 emotional reactivity and would contribute to the onset or exacerbation of an affective episode. This bias toward threatening information is in accordance with accounts that emphasize the influence of these pathogenic attentional biases on reactivity to stressful events for BD patients, even in asymptomatic patients and high-risk relatives (e.g., see Gotlib et al, 2005;Alloy et al, 2006). In this respect, Gotlib et al (2005) reported that, after the induction of a negative mood, the offspring of parents with BD exhibited an attentional bias toward threatening and manic-irritable information, but not toward positive or negative information.…”
Section: Stimulus Category Number Of Fixations (% Of Total)supporting
confidence: 85%
See 1 more Smart Citation
“…In these circumstances, the attentional preference toward threatening stimuli would increase the BD patients 0 emotional reactivity and would contribute to the onset or exacerbation of an affective episode. This bias toward threatening information is in accordance with accounts that emphasize the influence of these pathogenic attentional biases on reactivity to stressful events for BD patients, even in asymptomatic patients and high-risk relatives (e.g., see Gotlib et al, 2005;Alloy et al, 2006). In this respect, Gotlib et al (2005) reported that, after the induction of a negative mood, the offspring of parents with BD exhibited an attentional bias toward threatening and manic-irritable information, but not toward positive or negative information.…”
Section: Stimulus Category Number Of Fixations (% Of Total)supporting
confidence: 85%
“…This bias toward threatening information is in accordance with accounts that emphasize the influence of these pathogenic attentional biases on reactivity to stressful events for BD patients, even in asymptomatic patients and high-risk relatives (e.g., see Gotlib et al, 2005;Alloy et al, 2006). In this respect, Gotlib et al (2005) reported that, after the induction of a negative mood, the offspring of parents with BD exhibited an attentional bias toward threatening and manic-irritable information, but not toward positive or negative information. Furthermore, as indicated in Section 1, fMRI studies have shown a disturbance in neural activation during fear or threat processing across the different states of BD (including asymptomatic patients) using a variety of emotional paradigms (see Chen et al, 2006, for patients with mania and bipolar depression; see Wessa et al, 2007, for an example with euthymic patients).…”
Section: Stimulus Category Number Of Fixations (% Of Total)supporting
confidence: 85%
“…In particular, previous studies in BD have consistently shown a robust effect of negative stimuli on cognitive processing Passarotti et al 2011;Pavuluri et al 2012). Although current literature does not view such biases as primary endophenotypic markers of BD, both healthy pediatric BD offspring (Gotlib et al 2005) and adult siblings of BD patients exhibit affective processing biases toward negative stimuli in tasks of impulse control (Clark et al 2005;Klimes-Dougan et al 2006;Maziade et al 2009;Brand et al 2012). Similar to patients with BD, at-risk individuals display deficits in sustained attention and executive functioning (Zalla et al 2004;Frangou et al 2005;Klimes-Dougan et al 2006;Trivedi et al 2008;Kulkarni et al 2010;Diwadkar et al 2011) which suggests that cognitive deficits and affective processing biases could be interrelated, and may constitute markers of vulnerability to BD.…”
Section: Introductionmentioning
confidence: 87%
“…KlimesDougan et al [50] found that asymptomatic adolescent children of bipolar mothers showed deficits in executive functioning and selective deficits in spatial memory and attention in comparison with children of mothers with unipolar depression and without any disorder. Gotlib et al [51] found that, compared with normal controls, children of bipolar parents showed biases in attention and memory towards negative stimuli, similar to those found for bipolar and unipolar depressed adults, suggesting that children at increased risk for affective disorder are characterized by a negative cognitive style that can be activated by low mood. In a wide ranging review, Jones and Bentall [49] found that compared with normal controls, children of bipolar parents had higher levels of sensation seeking [52] and disinhibition [53], but also higher levels of creativity [54].…”
Section: Children Of Adults With Bipolar Disordermentioning
confidence: 95%